CuSeCN additive-based perovskite solar cell without hole transport layer and preparation method of CuSeCN additive-based hole transport layer-free perovskite solar cell

By using CuSeCN additive to perform P-type doping in perovskite solar cells, the problems of complex production steps, low efficiency and stability of perovskite solar cells are solved, and a perovskite solar cell with efficient, stable and simplified process is achieved.

CN119836206AActive Publication Date: 2025-04-15东方电气长三角(杭州)创新研究院有限公司

Patent Information

Application Number
CN202411772040.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-15
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing perovskite solar cells have complex production steps, low efficiency and stability, especially the cell efficiency and stability of hole-free transport layer structures are far behind conventional structures.

Method used

CuSeCN additive is used in the perovskite precursor solution to promote heteronucleation and eligible growth of perovskite crystals through strong coordination, so as to achieve P-type doping of perovskite films and improve the interfacial hole extraction and transmission capabilities.

Benefits of technology

The efficiency, stability and process reproducibility of perovskite solar cells without hole transport layer are significantly improved, the preparation process flow is simplified, and the manufacturing cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836206A_ABST
    Figure CN119836206A_ABST
Patent Text Reader

Abstract

The invention discloses a hole transport layer-free perovskite solar cell based on a CuSeCN additive and a preparation method, the perovskite solar cell comprises a transparent conductive substrate layer, a perovskite light absorption layer, an electron transport layer, an interface buffer layer and an electrode layer from bottom to top, and the perovskite light absorption layer contains the CuSeCN additive. According to the invention, a CuSeCN additive is adopted to carry out effective p-type doping on a lower interface perovskite thin film, SeCN-in CuSeCN and uncoordinated Pb < 2 + > form a strong bond action at a crystal boundary of the perovskite thin film, so that the SeCN-and the uncoordinated Pb < 2 + > serve as a perovskite electron acceptor, and the conversion of bottom perovskite from an n-type conductivity to a p-type conductivity is realized. Meanwhile, the introduction of CuSeCN effectively regulates and controls the crystallization kinetic process of perovskite, increases the grain size of perovskite, releases the tensile stress of perovskite crystal lattices at the bottom, forms a charge transfer interface with low defect state density, realizes an efficient and stable perovskite cell without a hole transport layer, and greatly promotes the industrialization process of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a CuSeCN additive-based perovskite solar cell without a hole transport layer and a preparation method thereof. Background Art

[0002] Organic-inorganic hybrid perovskite materials have attracted the attention of many researchers due to their excellent photoelectric properties, low cost, and wide sources. The photoelectric conversion efficiency of perovskite solar cells has soared from 3.8% in 2009 to 26.7% in 2024, catching up with the level of crystalline silicon solar cells currently on the market. It is considered to be the third-generation solar cell with the most commercial potential.

[0003] However, the production steps of efficient perovskite solar cells are usually complicated, requiring the sequential deposition of charge blocking layers, perovskite absorption layers, interface charge transport layers, and electrode layers. Shortening the production steps of perovskite solar cells without sacrificing the efficiency of perovskite solar cells will help reduce process complexity and manufacturing costs, thereby improving the large-scale batch manufacturing of perovskite solar cells.

[0004] In inverted perovskite cells without a hole transport layer, p-type additives such as 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane, fluorinated (tetraarylbenzo[1,2-b:4,5-b']dipyrrole-1,5-diylidene)dioxanesulfonate, and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid are usually added to the perovskite precursor solution to remove the hole transport layer deposition step, with the aim of modifying the energy level arrangement of the transparent conductive oxide / perovskite interface. However, the efficiency and stability of these perovskite cells without a hole transport layer are far behind those of conventional structure cells. In addition, conventional p-type dopants are prone to degradation under the action of light and heat, resulting in more deep energy level traps in the perovskite film, reducing the lattice stability of the perovskite material, and the corresponding long-term service life of the perovskite cell will also be greatly reduced. Summary of the invention

[0005] The purpose of the present invention is to address the deficiencies in the prior art and provide a perovskite solar cell without a hole transport layer based on a CuSeCN additive and a preparation method thereof. CuSeCN molecules are squeezed out from a precursor solution to the perovskite grain boundary and the bottom of the film, thereby achieving P-type doping of the buried interface perovskite film, improving the interface hole extraction and transmission capabilities, and improving the film-forming quality of the perovskite light-absorbing layer, thereby greatly improving the efficiency, stability and process reproducibility of the perovskite solar cell without a hole transport layer.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: as a first aspect, a hole transport layer-free perovskite solar cell based on CuSeCN additive, wherein the perovskite solar cell comprises, from bottom to top, a transparent conductive substrate layer, a perovskite light absorption layer, an electron transport layer, an interface buffer layer and an electrode layer, wherein the perovskite light absorption layer contains the CuSeCN additive.

[0007] As a second aspect, the present invention also provides a method for preparing a perovskite solar cell without a hole transport layer based on a CuSeCN additive, the method for preparing a perovskite solar cell comprising the following steps:

[0008] The perovskite powder is dissolved in an organic solvent, and after stirring and clarifying, a perovskite precursor solution is formed, so that the concentration of perovskite in the perovskite precursor solution is 0.1-3 mol / L; CuSeCN is added, and after complete dissolution, a perovskite precursor solution containing a CuSeCN additive is obtained, so that the concentration of CuSeCN in the perovskite precursor solution containing the CuSeCN additive is 0.001-50 mg / mL; the perovskite precursor solution containing the CuSeCN additive is coated or printed on a clean transparent conductive substrate, and a perovskite light absorbing layer is obtained after heat treatment;

[0009] An electron transport layer, an interface buffer layer and an electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a perovskite solar cell based on the CuSeCN additive.

[0010] Furthermore, the general structural formula of the perovskite is ABX3, wherein A is selected from Cs + 、MA + (CH3NH3 + ), FA + [HC(NH2)NH2 + ], B is selected from Pb 2+ Sn 2+ ,Ge 2+ , X is selected from I - Br - , Cl - .

[0011] Preferably, the concentration of perovskite in the perovskite precursor solution is 1.6 mol / L; the concentration of CuSeCN in the perovskite precursor solution containing the CuSeCN additive is 7.8 mg / mL.

[0012] Furthermore, the heat treatment temperature of the perovskite light absorbing layer is 30-300° C., and the time is 5-120 min; preferably, the treatment is performed at 100° C. for 30 min.

[0013] Furthermore, the transparent conductive substrate layer is selected from: FTO (fluorine-doped tin oxide) glass, ITO (tin-doped indium oxide) glass, ITO (tin-doped indium oxide) / PET (ethylene terephthalate), ITO (tin-doped indium oxide) / PEN (polyethylene phthalate), ITO (tin-doped indium oxide) / PI (polyimide); the electron transport layer is fullerene and its derivatives, including: C60, C70, PC60M; the interface buffer layer is selected from: bathocuproin, tin oxide, zinc oxide, yttrium oxide, cerium oxide, titanium oxide, niobium oxide; the electrode layer is selected from: Cu, Ag, Au, Mo, ITO (tin-doped indium oxide), IZO (zinc-doped indium oxide), AZO (aluminum-doped zinc oxide).

[0014] Preferably, the transparent conductive substrate layer is FTO glass; the electron transport layer is C60; the interface buffer layer is tin oxide; and the electrode layer is IZO.

[0015] Furthermore, the thickness of the perovskite light-absorbing layer containing the CuSeCN additive is 100 to 2000 nm; the thickness of the electron transport layer is 1 to 100 nm; the thickness of the interface buffer layer is 1 to 100 nm; and the thickness of the electrode layer is 10 to 10000 nm.

[0016] Preferably, the thickness of the perovskite light-absorbing layer containing the CuSeCN additive is 670 nm; the thickness of the electron transport layer is 20 nm; the thickness of the interface buffer layer is 20 nm; and the thickness of the electrode layer is 460 nm.

[0017] Furthermore, the electron transport layer is deposited by evaporation; the interface buffer layer is deposited by evaporation, sputtering, reactive plasma deposition, chemical vapor deposition, coating, and printing; the electrode layer is deposited by evaporation, sputtering, chemical vapor deposition, coating, and printing.

[0018] Preferably, the electron transport layer is deposited by evaporation; the interface buffer layer is deposited by chemical vapor deposition; and the electrode layer is deposited by sputtering deposition.

[0019] Furthermore, the organic solvent used to prepare the perovskite precursor solution is a mixture of one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 2-methoxyethanol, and acetonitrile in any ratio.

[0020] Preferably, the organic solvent used to prepare the perovskite precursor solution is a mixture of acetonitrile, N,N-dimethylformamide and N-methylpyrrolidone in a volume ratio of 3:6:1.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention uses CuSeCN to add to the perovskite precursor solution. On the one hand, SeCN - and Pb 2+ The strong coordination between them induces microclustering of the perovskite precursor, promotes the heterogeneous nucleation and preferential orientation growth of perovskite crystals, and increases the average grain size of the perovskite film. On the other hand, the selenium atoms and copper atoms in CuSeCN will respectively bind to the uncoordinated Pb 2+ and the hanging I - Strong bonding forms a local hole collection contact structure with good passivation effect, reduces non-radiative recombination, inhibits perovskite phase separation, and enhances the chemical structure stability of perovskite films.

[0023] 2. The CuSeCN additive molecules used in the present invention effectively fill the vacancies at the grain boundaries of the perovskite film, resulting in a decrease in the electron donor state density of the perovskite film and an increase in the hole concentration, thereby achieving good P-type doping of the bottom perovskite film. At the same time, the energy band bending at the interface of the CuSeCN-doped perovskite forms a good hole-selective contact, promotes the effective extraction and transfer of holes, eliminates the interface energy band barrier, releases the residual stress of the perovskite film, and improves the efficiency and stability of the device.

[0024] 3. The perovskite solar cell regulated by the CuSeCN additive in the present invention has the advantages of simple manufacturing process steps, high photoelectric conversion efficiency, good long-term working stability, and high preparation repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention is further described below in conjunction with the accompanying drawings and embodiments;

[0026] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell based on CuSeCN additives according to the present invention;

[0027] Figure 2 The SEM images of the perovskite light absorbing layer with or without CuSeCN additives of the present invention; wherein, (a) is the SEM image of the perovskite light absorbing layer without additives; (b) is the SEM image of the perovskite light absorbing layer with CuSeCN additives; (c) is the SEM image of the perovskite light absorbing layer with CuSCN additives; (d) is the SEM image of the perovskite light absorbing layer with Me-4PACz additives;

[0028] Figure 3 The transient fluorescence spectra of the perovskite light absorbing layer with and without the CuSeCN additive of the present invention;

[0029] Figure 4 The figure is a relationship diagram between the efficiency of the hole transport layer-free perovskite solar cell with CuSeCN additive and the storage time of the perovskite precursor solution of the present invention.

[0030] In the figure: transparent conductive substrate 1, perovskite light absorption layer 2, electron transport layer 3, interface buffer layer 4, electrode layer 5, CuSeCN additive 6. DETAILED DESCRIPTION

[0031] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention but not to limit the scope of the present invention.

[0032] The idea of ​​the present invention is to use CuSeCN additive to effectively dope the lower interface perovskite film with p-type. - With uncoordinated Pb 2+ A strong bond is formed at the grain boundary of the perovskite film, making it act as an electron acceptor for the perovskite, realizing the transition of the bottom perovskite from n-type to p-type conductivity. At the same time, the introduction of CuSeCN effectively regulates the perovskite crystallization kinetics, increases the perovskite grain size, releases the tensile stress of the bottom perovskite lattice, forms a charge transfer interface with low defect state density, and realizes an efficient and stable perovskite battery without a hole transport layer.

[0033] Embodiment 1:

[0034] like Figure 1 As shown, a hole transport layer-free perovskite solar cell based on CuSeCN additive and a preparation method thereof include the following steps:

[0035] Step 1: Steps for synthesizing CuSeCN:

[0036] 25.0 g (100 mmol) of CuSO4·5H2O was dissolved in 500 ml of deionized water, and then 25.0 g (100 mmol) of Na2S2O3·5H2O was added to the solution. The dark green solution was stirred continuously and cooled to 0°C. Then 9.7 g (67 mmol) of KSeCN aqueous solution was added dropwise. A blue-black precipitate began to precipitate. After continuous stirring for 40 minutes, the blue-black precipitate turned white. Finally, the white solid was filtered and washed twice with water, ethanol and ether in sequence. After vacuum drying at 70°C for 12 hours, an off-white CuSeCN powder (10 g, a yield of 89%) was obtained.

[0037] Step 2: Preparation of a hole transport layer-free perovskite solar cell containing CuSeCN additives:

[0038] (1) ultrasonically cleaning the FTO glass with a glass cleaning agent, ultrapure water, and alcohol in sequence, and drying after cleaning to obtain a clean FTO glass substrate;

[0039] (2) First, weigh CsI, MAI, FAI, and PbI2 powders (molar ratio of 0.1:0.1:0.8:1.08) and dissolve them in a mixed solvent of acetonitrile, N,N-dimethylformamide, and N-methylpyrrolidone in a volume ratio of 3:6:1. After stirring to clarify, a 1.6 mol / L perovskite precursor solution was obtained. Subsequently, 7.8 mg CuSeCN was weighed and added to 1 mL of the perovskite precursor solution. After stirring and dissolving completely, a perovskite precursor solution containing the CuSeCN additive was obtained.

[0040] (3) Slit coating a perovskite precursor solution containing a CuSeCN additive on a clean FTO glass substrate, and heat treating the coated perovskite wet film at 100°C for 30 min to obtain a perovskite light-absorbing layer with a thickness of 670 nm;

[0041] (4) A 20 nm thick C60 electron transport layer, a 20 nm thick tin oxide interface buffer layer, and a 460 nm thick IZO electrode layer are sequentially evaporated on the perovskite light absorbing layer, thereby obtaining a hole transport layer-free perovskite solar cell based on CuSeCN additives.

[0042] Comparative Example 1:

[0043] A CuSeCN additive-free perovskite solar cell without a hole transport layer and a preparation method thereof, comprising the following steps:

[0044] (1) ultrasonically cleaning the FTO glass with a glass cleaning agent, ultrapure water, and alcohol in sequence, and drying after cleaning to obtain a clean FTO glass substrate;

[0045] (2) First, weigh CsI, MAI, FAI, and PbI2 powders (molar ratio of 0.1:0.1:0.8:1.08) and dissolve them in a mixed solvent of acetonitrile, N,N-dimethylformamide, and N-methylpyrrolidone in a volume ratio of 3:6:1. After stirring to clarify, a 1.6 mol / L perovskite precursor solution is obtained. After stirring and dissolving completely, a perovskite precursor solution without CuSeCN additive is obtained.

[0046] (3) Slit coating a perovskite precursor solution on a clean FTO glass substrate, and heat treating the coated perovskite wet film at 100°C for 30 min to obtain a perovskite light-absorbing layer with a thickness of 670 nm;

[0047] (4) A 20 nm thick C60 electron transport layer, a 20 nm thick tin oxide interface buffer layer, and a 460 nm thick IZO electrode layer are sequentially evaporated on the perovskite light absorbing layer, thereby obtaining a hole transport layer-free perovskite solar cell without CuSeCN additives.

[0048] Comparative Example 2:

[0049] A CuSCN additive-based perovskite solar cell without a hole transport layer and a preparation method thereof, comprising the following steps:

[0050] (1) ultrasonically cleaning the FTO glass with a glass cleaning agent, ultrapure water, and alcohol in sequence, and drying after cleaning to obtain a clean FTO glass substrate;

[0051] (2) First, weigh CsI, MAI, FAI, and PbI2 powders (molar ratio of 0.1:0.1:0.8:1.08) and dissolve them in a mixed solvent of acetonitrile, N,N-dimethylformamide, and N-methylpyrrolidone in a volume ratio of 3:6:1. After stirring to clarify, a 1.6 mol / L perovskite precursor solution was obtained. Subsequently, 11.7 mg CuSCN was weighed and added to 1 mL of the perovskite precursor solution. After stirring and dissolving completely, a perovskite precursor solution containing the CuSCN additive was obtained.

[0052] (3) Slit coating a perovskite precursor solution containing a CuSCN additive on a clean FTO glass substrate, and heat treating the coated perovskite wet film at 100°C for 30 min to obtain a perovskite light-absorbing layer with a thickness of 670 nm;

[0053] (4) A 20 nm thick C60 electron transport layer is evaporated on the perovskite light absorbing layer, a 20 nm thick tin oxide interface buffer layer is atomically deposited, and a 460 nm thick IZO electrode layer is sputtered to obtain a hole transport layer-free perovskite solar cell based on the CuSCN additive.

[0054] Comparative Example 3:

[0055] A hole transport layer-free perovskite solar cell based on [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) additive and a preparation method thereof, comprising the following steps:

[0056] (1) ultrasonically cleaning the FTO glass with a glass cleaning agent, ultrapure water, and alcohol in sequence, and drying after cleaning to obtain a clean FTO glass substrate;

[0057] (2) First, weigh CsI, MAI, FAI, and PbI2 powders (molar ratio of 0.1:0.1:0.8:1.08) and dissolve them in a mixed solvent of acetonitrile, N,N-dimethylformamide, and N-methylpyrrolidone in a volume ratio of 3:6:1. After stirring to clarify, a 1.6 mol / L perovskite precursor solution was obtained. Subsequently, 3.2 mg Me-4PACz was weighed and added to 1 mL of the perovskite precursor solution. After stirring and dissolving completely, a perovskite precursor solution containing the Me-4PACz additive was obtained.

[0058] (3) Slit coating a perovskite precursor solution containing Me-4PACz additive on a clean FTO glass substrate, and heat treating the coated perovskite wet film at 100°C for 30 min to obtain a perovskite light-absorbing layer with a thickness of 670 nm;

[0059] (4) A 20 nm thick C60 electron transport layer, a 20 nm thick tin oxide interface buffer layer, and a 460 nm thick IZO electrode layer were sequentially evaporated on the perovskite light absorbing layer to obtain a hole transport layer-free perovskite solar cell based on Me-4PACz additive.

[0060] Comparative Example 4:

[0061] A perovskite solar cell based on a CuSeCN hole transport layer and a preparation method thereof, comprising the following steps:

[0062] Step 1: Steps for synthesizing CuSeCN:

[0063] 25.0 g (100 mmol) of CuSO4·5H2O was dissolved in 500 ml of deionized water, and then 25.0 g (100 mmol) of Na2S2O3·5H2O was added to the solution. The dark green solution was stirred continuously and cooled to 0°C. Then 9.7 g (67 mmol) of KSeCN aqueous solution was added dropwise. A blue-black precipitate began to precipitate. After continuous stirring for 40 minutes, the blue-black precipitate turned white. Finally, the white solid was filtered and washed twice with water, ethanol and ether in sequence. After vacuum drying at 70°C for 12 hours, an off-white CuSeCN powder (10 g, a yield of 89%) was obtained.

[0064] Step 2: Preparation of perovskite solar cells based on CuSeCN hole transport layer:

[0065] (1) ultrasonically cleaning the FTO glass with a glass cleaning agent, ultrapure water, and alcohol in sequence, and drying after cleaning to obtain a clean FTO glass substrate;

[0066] (2) Weigh CuSeCN and dissolve it in a mixed solvent of water:ethanolamine:ethylenediamine:diethanolamine in a volume ratio of 2:6:1:1 to form a 20 mg / mL CuSeCN solution. Slit-coat the CuSeCN solution on a clean FTO glass substrate layer. After coating, heat treat at 300°C for 30 min to obtain a 25 nm CuSeCN hole transport layer.

[0067] (3) First, weigh CsI, MAI, FAI, and PbI2 powders (molar ratio of 0.1:0.1:0.8:1.08) and dissolve them in a mixed solvent of acetonitrile, N,N-dimethylformamide, and N-methylpyrrolidone in a volume ratio of 3:6:1. After stirring to clarify, a 1.6 mol / L perovskite precursor solution was obtained. After stirring and dissolving completely, a perovskite precursor solution was obtained.

[0068] (4) Slit coating a perovskite precursor solution on a FTO glass substrate covered with a CuSeCN hole transport layer, and heat treating the coated perovskite wet film at 100° C. for 30 min to obtain a perovskite light absorbing layer with a thickness of 670 nm;

[0069] (5) A 20 nm thick C60 electron transport layer is evaporated on the perovskite light absorbing layer, a 20 nm thick tin oxide interface buffer layer is atomically layer deposited, and a 460 nm thick IZO electrode layer is sputtered to obtain a perovskite solar cell based on a CuSeCN hole transport layer.

[0070] As shown in Table 1, the photoelectric conversion efficiency of the hole transport layer-free perovskite solar cell prepared with CuSeCN additive is as high as 24.95%, and the efficiency of the cell only decays by 2.1% after 1000 hours of maximum power point tracking. The device efficiency and stability are much better than other comparative devices, indicating that the addition of CuSeCN to the perovskite precursor solution can achieve the effective doping of CuSeCN with the bottom perovskite, induce rapid heterogeneous nucleation of perovskite, improve the crystallization quality of the perovskite film, eliminate the buried interface defect recombination center, prolong the interface carrier transmission life, and simultaneously improve the efficiency and stability of the perovskite cell.

[0071] Table 1. Performance parameters of the devices in the examples and comparative examples

[0072]

[0073] like Figure 2 As shown, the perovskite film prepared from the perovskite precursor solution with CuSeCN additive has large grain size and high crystallinity, and the CuSeCN molecules can be effectively enriched at the grain boundaries of the film.

[0074] like Figure 3 As shown, the perovskite light-absorbing layer containing CuSeCN additives exhibits an ultra-long transient fluorescence lifetime, indicating that the addition of CuSeCN can eliminate the defect-induced charge recombination centers of the perovskite film, inhibit the non-radiative recombination of carriers in the film, and increase the carrier diffusion length.

[0075] like Figure 4As shown, the perovskite precursor solution using CuSeCN additive also exhibits excellent solution storage stability. Even if the perovskite precursor solution is placed for 3 weeks, device performance comparable to that of fresh perovskite solution can still be prepared, which greatly improves the consistency of the preparation process of perovskite cells without hole transport layer and provides strong guarantee for the mass production of perovskite cells.

[0076] Finally, combine Figure 2-4 As shown, it shows that the addition of CuSeCN causes the energy band at the interface between the perovskite and the transparent conductive oxide anode to bend upward, the maximum value of the perovskite valence band becomes shallower, and a perovskite / anode interface with energy level matching is formed, which enables the extraction of holes inside the perovskite and their efficient transmission to the anode without relying on a hole transport layer, improves the film quality of the perovskite film and reduces the charge recombination in the perovskite film, thereby preparing an efficient and stable perovskite solar cell without a hole transport layer, greatly simplifying the battery preparation process, reducing the battery production cost, and promoting the industrialization of perovskite solar cells.

[0077] The above description is only a preferred experimental example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A perovskite solar cell without hole transport layer based on CuSeCN additive, characterized in that: The perovskite solar cell comprises a transparent conductive substrate layer, a perovskite light absorbing layer, an electron transport layer, an interface buffer layer and an electrode layer from bottom to top, wherein the perovskite light absorbing layer contains a CuSeCN additive.

2. A method for preparing a perovskite solar cell without a hole transport layer based on CuSeCN additive, characterized in that: The method for preparing the perovskite solar cell comprises the following steps: The perovskite powder is dissolved in an organic solvent, and after stirring and clarifying, a perovskite precursor solution is formed, so that the concentration of perovskite in the perovskite precursor solution is 0.1-3 mol / L; CuSeCN is added, and after complete dissolution, a perovskite precursor solution containing a CuSeCN additive is obtained, so that the concentration of CuSeCN in the perovskite precursor solution containing the CuSeCN additive is 0.001-50 mg / mL; the perovskite precursor solution containing the CuSeCN additive is coated or printed on a clean transparent conductive substrate, and a perovskite light absorbing layer is obtained after heat treatment; An electron transport layer, an interface buffer layer and an electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a perovskite solar cell based on the CuSeCN additive.

3. The method for preparing a perovskite solar cell without a hole transport layer based on CuSeCN additive according to claim 2, characterized in that: The general structural formula of the perovskite is ABX3, wherein A is selected from Cs + 、MA + , FA + , B is selected from Pb 2+ Sn 2+ ,Ge 2 + , X is selected from I - Br - , Cl - .

4. The method for preparing a perovskite solar cell without a hole transport layer based on CuSeCN additive according to claim 2, characterized in that: The heat treatment temperature of the perovskite light absorbing layer is 30 to 300° C., and the time is 5 to 120 minutes.

5. The method for preparing a perovskite solar cell without a hole transport layer based on CuSeCN additive according to claim 2, characterized in that: The transparent conductive substrate layer is selected from: FTO glass, ITO glass, ITO / PET, ITO / PEN, ITO / PI; the electron transport layer is fullerene and its derivatives, including: C60, C70, PC60M; the interface buffer layer is selected from: bathocuproin, tin oxide, zinc oxide, yttrium oxide, cerium oxide, titanium oxide, niobium oxide; the electrode layer is selected from: Cu, Ag, Au, Mo, ITO, IZO, AZO.

6. The method for preparing a perovskite solar cell without a hole transport layer based on CuSeCN additive according to claim 2, characterized in that: The thickness of the perovskite light-absorbing layer containing the CuSeCN additive is 100 to 2000 nm; the thickness of the electron transport layer is 1 to 100 nm; the thickness of the interface buffer layer is 1 to 100 nm; and the thickness of the electrode layer is 10 to 10000 nm.

7. The method for preparing a perovskite solar cell without a hole transport layer based on CuSeCN additive according to claim 2, characterized in that: The electron transport layer is deposited by evaporation; The deposition methods of the interface buffer layer include: evaporation, sputtering, reactive plasma deposition, chemical vapor deposition, coating, and printing; the deposition methods of the electrode layer include: evaporation, sputtering, chemical vapor deposition, coating, and printing.

8. The method for preparing a perovskite solar cell without a hole transport layer based on CuSeCN additive according to any one of claims 5 to 7, characterized in that: The transparent conductive substrate layer is FTO glass; the electron transport layer is C60; the interface buffer layer is tin oxide; the electrode layer is IZO; the thickness of the perovskite light absorption layer containing the CuSeCN additive is 670nm; the thickness of the electron transport layer is 20nm; the thickness of the interface buffer layer is 20nm; the thickness of the electrode layer is 460nm; the electron transport layer is deposited by evaporation; the interface buffer layer is deposited by chemical vapor deposition; and the electrode layer is deposited by sputtering deposition.

9. The method for preparing a perovskite solar cell without a hole transport layer based on CuSeCN additive according to claim 2, characterized in that: The organic solvent used to prepare the perovskite precursor solution is a mixture of one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 2-methoxyethanol and acetonitrile in any proportion.

10. The method for preparing a perovskite solar cell without a hole transport layer based on CuSeCN additive according to claim 2 or 9, characterized in that: The concentration of perovskite in the perovskite precursor solution is 1.6 mol / L; the concentration of CuSeCN in the perovskite precursor solution containing the CuSeCN additive is 7.8 mg / mL; the organic solvent used to prepare the perovskite precursor solution is a mixture of acetonitrile, N,N-dimethylformamide and N-methylpyrrolidone in a volume ratio of 3:6:1.

Citation Information

Patent Citations

  • Functionalized perovskite material based on novel ionic liquid and application of functionalized perovskite material in solar cell preparing

    CN107337644A

  • Perovskite precursor solution, perovskite solar cell and preparation method

    CN118742174A

  • Preparation method of p-type semiconductor film, p-type semiconductor film, manufacturing method of perovskite solar cell, and perovskite solar cell

    JP2024027324A

Cited By

  • Method for stabilizing ABX3 type perovskite semiconductor material through self-polarized nanocrystalline

    CN121099877A